2020
DOI: 10.3389/fnins.2020.00049
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocinergic Cells of the Hypothalamic Paraventricular Nucleus Are Involved in Food Entrainment

Abstract: When food is presented at a specific time of day subjects develop intense locomotor behavior before food presentation, termed food anticipatory activity (FAA). Metabolic and hormonal parameters, as well as neural structures also shift their rhythm according to mealtime. Food-entrained activity rhythms are thought to be driven by a distributed system of central and peripheral oscillators sensitive to food cues, but it is not well understood how they are organized for the expression of FAA. The hormone Oxytocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 35 publications
6
11
2
Order By: Relevance
“…In contrast to the previously well known activation of OT cells after food intake, recently we reported that a particular subpopulation of oxytocinergic cells in the posterior region of the paraventricular hypothalamus in the rabbit pup shows a clear activation in anticipation to their only daily episode of food ingestion 10 . Rabbit pups ingest food only once a day and had been recognized as a natural model of food entrainment 11,12 .…”
Section: Introductioncontrasting
confidence: 99%
“…In contrast to the previously well known activation of OT cells after food intake, recently we reported that a particular subpopulation of oxytocinergic cells in the posterior region of the paraventricular hypothalamus in the rabbit pup shows a clear activation in anticipation to their only daily episode of food ingestion 10 . Rabbit pups ingest food only once a day and had been recognized as a natural model of food entrainment 11,12 .…”
Section: Introductioncontrasting
confidence: 99%
“…In spite of these findings the PVN still presents an attractive possibility for being part of the FEO. For example, oxytocin (OT) has recently been postulated as the main hormonal cue for FAA due to findings linking food entrainment in rabbits to OT-PVN neurons [119]. Although the SCN has direct projections to the PVN, the PVN neuroendocrine neurons are also indirectly modulated by the SCN via its innervation of the DMH, ARC and MPOA [120,121].…”
Section: Feeding and The Circadian Clock In Neuronal Subtypes Of The Lh Pvn Dmh And Vmhmentioning
confidence: 99%
“… Spetter and Hallschmid, 2017 ; McCormack et al, 2020 ). However, in the main body of the PVN, specifically in its dorsal and ventral portion and in its caudal region, we found an activation of OT cells before milk ingestion in the rabbit ( Caba et al, 2020 ). In Figure 2 , we show this effect in the two subregions of the main body of the PVN.…”
Section: Oxytocin and A Central And Peripheral Network In Food Entraimentioning
confidence: 63%
“…In the rat under food restriction, and in the rabbit pup before their daily period of milk intake, there is an increase in corticosterone, free fatty acids and glucagon indicating a catabolic state, and in parallel there is a decrease in glycogen and insulin (Díaz-Muñoz et al, 2000;Escobar et al, 2000;Morgado et al, 2008Morgado et al, , 2010. We proposed (Caba et al, 2020) that the subpopulation of activated neurons A-F: Expression of oxytocin (white arrows) and double-labeled oxytocin and Fos (black arrows)-ir cells in the PVNmd (A,C,E) and PVNmv (B,D,F) just before nursing at 10:00 am (N10:00), 1.5 h after (N11:30) and in fasted subjects at the time of the previous scheduled nursing (F10:00). Note the increase in Fos/OT-ir cells before nursing (A) that persist in fasted subjects (E) only in the PVNmd.…”
Section: Oxytocin and A Central And Peripheral Network In Food Entrainmentmentioning
confidence: 94%
See 1 more Smart Citation